Moderating Competitive Advantage On Factors Affecting Economic Performance - Eksandy, Arry; Paramitha Sofia, Irma (International Journal of Educational Research & Social Sciences, 2022)
The purpose of this study is to determine the effect of environmental performance, corporate image, corporate social performance on economic performance with competitive advantage as a moderating. The population of this study includes all manufacturing company listed on the Indonesia Stock Exchange in the 2014-2018 period. The sampling technique used purposive sampling technique. Based on predetermined criteria obtained 11 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data logistic regression analysis. The results showed that environmental performance, corporate social performance, competitive advantage proxied by economic performance had a negatif effect, corporate imageproxied by economic performance had no effect. While environmental performance, corporate social performance proxied by economic performance had a positif effect after moderating by competitive advantage, corporate imageproxied by economic performance had no effecteffect after moderating by competitive advantage.